The understanding of nonverbal communication skills among secondary school students towards teaching and learning / Mohd Shahnawi Muhmad Pirus and Syed Faizal Sitheek Rahman - Muhmad Pirus, Mohd Shahnawi; Rahman, Syed Faizal Sitheek (Centre for Media and Information Warfare Studies, 2020)
This qualitative study focuses on understanding the types, factors and outcomes of nonverbal communication skills that can be used by speakers to give meaningful teaching and learning session towards their students. To gain insights about the core focus of this study, three research questions were laid out which are (1) what are nonverbal communication skills being used by speakers towards teaching and learning in secondary schools, (2) what are the factors contributing to the preferred nonverbal communication skills applied by the speakers, (3) what are the outcomes of nonverbal communication skills towards secondary school students. This study was guided with the theory of Communication model by Albert Mehrabian [9] from his book named Silent messages. Using the phenomenology approach, several findings were gathered through in-depth interviews with seven informants who are secondary school students located in Klang and Kajang. Data analysis were conducted simultaneously with the data that was collected and with the help of computer software NVivo 11.0 for the process of coding. Thematic analysis and constant comparison strategy also were used to analyze the data that was gathered. The result of this study revealed that the five nonverbal communication components which are body movement, facial expression, visual aids, hand gestures and voice intonation were found to be highly important and preferred by students. There are some internal and external contributing factors that influences speakers to use certain type of body language and lastly the outcomes of the nonverbal communications skills led to the understanding, liking, focus, memory recalling and excitement towards their teaching and learning strategy.